Rekonstruksi Paradigma Kualitas Layanan Pendidikan Berbasis Teori Service Quality dalam Meningkatkan Kepuasan Peserta Didik: Studi Literatur Sistematis - Firman Aulia Ramadhan; Heru Tri Ahmanto (Jurnal Pendidikan, Sejarah, dan Budaya, 2026)
This study aims to reconstruct the paradigm of educational service quality based on service quality theory in enhancing student satisfaction through a systematic literature review approach. The data were derived from reputable scholarly articles indexed in Scopus, Web of Science, and SINTA, as well as relevant academic books published within the last decade. The analysis employed the PRISMA framework and thematic analysis to identify conceptual patterns and relationships among variables. The findings indicate that educational service quality is multidimensional, encompassing managerial, pedagogical, cultural, psychological, and technological aspects. The relationship between service quality and student satisfaction is complex and mediated by learning experiences and pedagogical interactions. The reconstructed paradigm proposes an integrative model positioning educational services as a relational system grounded in meaningful learning experiences. This study contributes theoretically by strengthening the conceptual framework of educational service quality and methodologically by applying a systematic literature review in conceptual analysis.